WEB-Spline-based mesh-free finite element approximation for p-Laplacian. Issue 6 (2nd June 2016) - Chaudhary, Sudhakar; Srivastava, Vimal; Kumar, V.V.K Srinivas; Srinivasan, Balaji
Abstract : In this paper, we discuss the approximation of p -Laplace problem using WEB-Spline based mesh free finite elements. Along with usual weak formulation, we also consider the mixed formulation of the p -Laplace problem. We give existence, uniqueness results for both continuous and discrete problems. We also provide a priori error estimates for both the formulations.